Understanding differences in labour market attachment of single mothers in Great Britain and West Germany - Zagel, Hannah (Berlin, 2015)
"This paper investigates the relationships between single mothers’ demographic and socio-economic circumstances and differences in their labour market attachment in Great Britain and West Germany. Employment of single mothers is a key issue in current policy debates in both countries, as well as in welfare state research. The heterogeneity of the group of women who experience single motherhood poses a challenge to contemporary social policy. To complicate the matter, single motherhood is not static but a result of family life dynamics. This paper provides an empirical insight into differences in labour market attachment of single mothers, investigating the demographic and socio-economic factors that distinguish careers dominated by full-time, part-time or non-employment. Considering 10-18 years of women’s careers, data from the British Household Panel Survey (1991-2008) and the German Socio-Economic Panel (1991-2008) (N= 678) are used for regression analysis. The findings suggest that, in both countries, young single mothers experience longer periods of non-employment. Vocational qualifications go together with part-time careers while high education attainments and school-age children allow for full-time employment. Part-time employment is a less common track for British compared to West German single mothers."